1642b Education and training in recognition, surveillance and prevention of occupational diseases. (24th April 2018) - van der Laan, G; van Dijk, F
Abstract : Introduction: There is a huge global need for good education, training and information on Occupational Safety and Health. Especially for tracing and prevention of occupational diseases. Internet can accelerate the process and coverage of education and training. In this session experiences in international projects will be shared. Methods: A range of activities in this field will be presented, especially from LDOH (www.ldoh.net): Development of online, blended and other materials for information and education, training courses on recognition, health surveillance, diagnosis, therapy and prevention of work–related diseases. Good practices like international summer school activities and Question and Answer facilities. New efforts involving primary or community health care as the foundation for basic occupational health care: Turkey, Thailand, Brazil, Vietnam, Iran, parts in China, new efforts in India, Bangladesh, South Africa. Results and discussion: Education and training in OHS is not a standalone activity. It should be programmatic and on many different levels, involving everyone who can be involved: vocational schools, using participatory approaches empowering communities and even including churches and private companies. Importance of OSH infrastructure (sector–wise, regional or national programs; involvement of Labour Inspection and Social Security Organisations), multidisciplinary collaboration and outreach–activities towards the entire global working population: all formal and informal workers with special attention for vulnerable groups (women, children, migrants, elderly): Universal Health Coverage (WHO). A more active role of International bodies?